Mycobacterium abscessus Complex Infections: A Retrospective Cohort Study. (9th February 2018) - Sfeir, Maroun; Walsh, Marissa; Rosa, Rossana; Aragon, Laura; Liu, Sze Yan; Cleary, Timothy; Worley, Marylee; Frederick, Corey; Abbo, Lilian M
Abstract: Background: Infections caused by Mycobacterium abscessus group strains are usually resistant to multiple antimicrobials and challenging to treat worldwide. We describe the risk factors, treatment, and clinical outcomes of patients in 2 large academic medical centers in the United States. Methods: A retrospective cohort study of hospitalized adults with a positive culture for M. abscessus in Miami, Florida (January 1, 2011, to December 31, 2014). Demographics, comorbidities, the source of infection, antimicrobial susceptibilities, and clinical outcomes were analyzed. Early treatment failure was defined as death and/or infection relapse characterized either by persistent positive culture for M. abscessus within 12 weeks of treatment initiation and/or lack of radiographic improvement. Results: One hundred eight patients were analyzed. The mean age was 50.81 ± 21.03 years, 57 (52.8%) were females, and 41 (38%) Hispanics. Eleven (10.2%) had end-stage renal disease, 34 (31.5%) were on immunosuppressive therapy, and 40% had chronic lung disease. Fifty-nine organisms (54.6%) were isolated in respiratory sources, 21 (19.4%) in blood, 10 (9.2%) skin and soft tissue, and 9 (8.3%) intra-abdominal. Antimicrobial susceptibility reports were available for 64 (59.3%) of the patients. Most of the isolates were susceptible to clarithromycin, amikacin, and tigecycline (93.8%, 93.8%, and 89.1%, respectively). None of the isolates were susceptible to trimethoprim/sulfamethoxazole, and only 1 (1.6%) was susceptible to ciprofloxacin. Thirty-six (33.3%) patients early failed treatment; of those, 17 (15.7%) died while hospitalized. On multivariate analysis, risk factors significantly associated with early treatment failure were disseminated infection (odds ratio [OR], 11.79; 95% confidence interval [CI], 1.53–81.69; P = .04), acute kidney injury (OR, 6.55; 95% CI, 2.4–31.25; P = .018), organ transplantation (OR, 2.37; 95% CI, 2.7–23.1; P = .005), immunosuppressive therapy (OR, 2.81; 95% CI, 1.6–21.4; P = .002), intravenous amikacin treatment (OR, 4.1; 95% CI, 0.9–21; P = .04), clarithromycin resistance (OR, 79.5; 95% CI, 6.2–3717.1, P < .001), and presence of prosthetic device (OR, 5.43; 95% CI, 1.57–18.81; P = .008). Receiving macrolide treatment was found to be protective against early treatment failure (OR, 0.13; 95% CI, 0.002–1.8; P = .04). Conclusions: Our cohort of 108 M. abscessus complex isolates in Miami, Florida, showed an in-hospital mortality of 15.7%. Most infections were respiratory. Clarithromycin and amikacin were the most likely agents to be susceptible in vitro. Resistance to fluoroquinolone and trimethoprim/sulfamethoxazole was highly common. Macrolide resistance, immunosuppression, and renal disease were significantly associated with early treatment failure.